Lola at the Library - McQuinn, Anna; Beardshaw, Rosalind (Watertown, MA : Charlesbridge, 2006)
Every Tuesday Lola and her mother visit their local library to return and check out books, attend story readings, and share a special treat.
Keywords: Libraries -- Juvenile fiction; Books and reading -- Juvenile fiction; African Americans -- Juvenile fiction; Libraries -- Fiction; Books and reading -- Fiction; African Americans -- Fiction